Pengaruh Pajak terhadap Distribusi Pendapatan: (Studi Kasus di Negara Berkembang) - Azza Bunaia; Artika Tri Septia; Ahmad Wahyudi Zein (Jurnal Ilmiah Ekonomi, Akuntansi, dan Pajak, 2025)
This article discusses the effect of tax policy on income distribution in developing countries. Tax is a fiscal instrument that is not only used to finance state expenditure, but also as a tool to reduce economic inequality. This study analyzes how progressive tax system, income tax collection, and consumption tax impact income redistribution in several developing countries. The secondary data used comes from World Bank, IMF, and other scholarly publications. The analysis shows that fair and progressive tax policies can help reduce income inequality. However, many developing countries face challenges in implementing effective tax systems, including low compliance and regressive tax structures. Therefore, comprehensive fiscal policy reforms are needed so that taxes can truly serve as an effective income distribution tool.